Motif Ii of Japanese Encephalitis Vius Ns3 Pro is Not Essential for Rna Binding Activit - Utama, Andi; Shimizu, Hiroyuki (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2007)
The role of motif n (DEAR AsPw-GlulK,,-Ala.,.7-Hi 1 ) of Japanese encephalitis virus (JEV) NS3 protein on RNA binding activity was studied. A point mutation was introduced to the motif and the RNA binding activity of each mutant protein was analyzed. Truncated form of each protein with a His-tag was expressed m Escherichia coli BL2l(DE3) pLysS and purified by metal affinity resin. Asp-285 - and Glu-286 was respectively substituted with Ala, AJa-287 was replaced by Cys.,Gly. or ser. His-288 was mutated to other 19 amino acids. In total. 24 mutant proteins were produced and analyzed. AL results, all mutants showed quite similar RNA binding activity. Indicating that motif II of JEY NS3 is not related to RNA binding activity. The same finding was reported for hepatitis C virus c (Hey) NS3 protein, suggesting the similar structure of NS3 protein in flavivirus .Keywords: Japanese encephalitis, R.binding, motif